articel ANALYZING THE ADOPTION OF CLOUD-BASED ACCOUNTING SYSTEMS AND THEIR IMPACT ON SMALL BUSINESS EFFICIENCY - Nia Riana; Wawan Ichwanudin; Ijang Faisal (PT. Kreatif Indonesia Satu, 2024)
Background Small businesses are vital contributors to global economies but often face challenges in managing financial processes due to resource limitations and lack of technical expertise. Traditional accounting systems, while reliable, demand significant investments and are prone to errors when used manually. The advent of cloud-based accounting systems (CBAS) offers a solution, providing small businesses with affordable, scalable, and efficient tools to manage their financial operations. However, despite their potential, the adoption of CBAS remains uneven, with many businesses hesitant due to perceived barriers like data security concerns and lack of technical knowledge. Aims This study aims to: Investigate the key drivers and barriers influencing the adoption of CBAS among small businesses. Analyze the impact of CBAS on financial accuracy, operational efficiency, and compliance. Highlight the role of training and technical support in ensuring successful CBAS adoption. Provide practical insights through case studies of businesses that have successfully integrated CBAS. Offer recommendations to stakeholders for promoting broader adoption and maximizing the benefits of CBAS. Research Method The study employed a mixed-methods approach, combining quantitative and qualitative techniques to provide a comprehensive analysis. A survey was conducted among 250 small business owners across various industries to gather quantitative data on adoption drivers, barriers, and impacts. In addition, 30 in-depth interviews were carried out to gain qualitative insights into the experiences and perceptions of CBAS users. The research also incorporated secondary data from industry reports, case studies, and academic literature to triangulate findings. The Technology Acceptance Model (TAM) and Diffusion of Innovation (DOI) theory provided the theoretical frameworks for analyzing the results. Results and Conclusion CBAS adoption is primarily driven by ease of use, cost-effectiveness, and competitive advantage, but is hindered by concerns over data security, lack of technical expertise, and perceived complexity. Businesses that adopted CBAS reported a 35% reduction in accounting errors, improved compliance with tax regulations, and enhanced decision-making capabilities. Operational efficiency significantly improved, with time savings averaging 20 hours per month and optimized workflows leading to better resource utilization. Training and technical support were identified as critical factors in overcoming barriers and ensuring successful adoption. Conclusion: CBAS offers transformative benefits for small businesses, including improved accuracy, efficiency, and compliance. However, addressing barriers such as knowledge gaps and security concerns is essential to realize its full potential. The study highlights the need for collaborative efforts among CBAS providers, policymakers, and small businesses to foster broader adoption and leverage the advantages of cloud-based technologies.